Development of an optical pH measurement system based on colorimetric effect - Puteri Nur Syahirah Mohamed Mustafa; Aiman Shahmi Azam; Mohd Suhaimi Sulaiman; Ahmad Fairuz Omar; Mohamad Faizal Abd Rahman (Institute of Advanced Engineering and Science, 2021)
This paper proposed an optical pH measurement system developed to measure the changes of pH levels based on colorimetric reactions with phenol red reagent. The optical sensing was achieved through the implementation of a pair of light emitting diode (LED) and photodiode. The detection mechanism was based on different absorbance of light intensity at pH values of 2.36, 8.32, 9.08 and 12.83. The data processing method was carried out using LabVIEW software and interfaced with NI USB DAQ 6008. The measured voltage showed a good correlation in relation to the pH level with R2 equals to 0.9624. This relationship was used as a calibration curve in the final system testing. The final measurement of pH showed a good agreement between the actual and measured values with an error of less than 5%, thus indicating the reliability of the proposed system.